Pension and Intergenerational Balance - A case study of Norway, Poland and Germany using Generational Accounting - Natalie Laub; Christian Hagist (Intergenerational Justice Review)
In this paper we apply the method of Generational Accounting to analyse whether today’s government policy burdens future generations with a heavier load than current generations. We analyse pay-as-you-go pension systems and their reforms in Norway, Poland and Germany. Our results show that, through these reforms, pension systems in all three countries became more intergenerationally balanced as the implicit debt to be paid by future generations was reduced. However, the burden is shared differently: in Norway current pensioners have to contribute to enhancing the financial sustainability of the pension system while Poland and Germany seem to protect current pensioners at the expense of younger generations.